Sentiment Analysis on PeduliLindungi Application Using TextBlob and VADER Library - Fathonah Illia; Migunani Puspita Eugenia; Sita Aliya Rutba (Politeknik Statistika STIS, 2021)
The Covid-19 virus has become a global pandemic, including Indonesia. Various efforts have been made by the Government to reduce the negative impact by this pandemic, one of which is through the PeduliLindungi application. The research was conducted to obtain public sentiment towards the application by using twitter data. The data collection period is from August 31 to September 7, 2021, this period was chosen due to the emergence of news regarding vaccine data leaks associated with data leaks in the PeduliLindung application. Sentiment analysis is carried out using the TextBlob and VADER libraries. The results of this sentiment analysis are sufficient to display public opinion and it is hoped that decision makers can improve applications based on these opinions. Then, it was found that the VADER library can be said to be better in conducting sentiment analysis in research because the lexicon approach used is based on social media.